(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The search for new forms and methods of education remains one of the most important challenges of our time. Therefore, it is crucial for the education sector to develop new methods and tools that take into account the needs of the modern generation and integrate them with existing innovations. One such emerging area is gamification. Gamification is a technology for the effective use of game elements in other areas. This is especially important in the educational process against the backdrop of today’s growing information flow. Gaming techniques and technologies have been used in pedagogical practice since ancient times. Along with work and study, play is one of the fundamental types of human activity, stemming from the need for play. The importance and effectiveness of gaming practices in various fields of culture have been and are being studied by scholars in philosophy, philology, sociology, political science, psychology, and other fields. The current stage of development of the humanities is characterized by the emergence of games as a basis for innovation and a stimulus for creative thinking. Game studies is an interdisciplinary field of research. The first analysis of games and their impact on culture and social life was reflected in the work of philosopher Johannes Huizinga in 1938, author of the treatise "Homo Ludens," which examined the significance of games. Huizinga argues in his study that "it is impossible to transform games into cultural phenomena, since they are even older than them and have already been observed in animals. On the contrary, culture itself (speech, myth, cult, science) has a more playful character." This interest in games as a cultural shaping factor in history is not accidental, according to the author, as people interact with games throughout their lives.